Kecerdasan Emosional, Motivasi, dan Organizational Citizenship Behavior terhadap Efektivitas Kerja Pegawai - Shalsabila, Shinta; Fahlevi, Alvin (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to examine and analyze the effect of Emotional Intelligence, Motivation and Organizational Citizenship Behavior on employee work effectiveness (a case study at the Control and Order Division of the Medan City Department of Transportation). The sample used in this study were 104 employees at the Medan City Transportation Agency. This research was conducted at the Medan City Transportation Service Office, which is located at Jalan Imam Bonjol No.61 Suka Damai, Medan Polonia, Medan City, North Sumatra 20157. This research is planned from March 2020 to May 2020. The Emotional Intelligence variable has a t-count value of 8,962, which means that the t-count is greater than the t-table value which is 1.9837 and has a sig value. t for emotional intelligence variable of 0.000 is smaller than alpha of 0.05. This shows that the emotional intelligence variable has a positive influence on the effectiveness of employees at the Medan City Transportation Agency. Then the alternative hypothesis is accepted. The motivation variable has a t-count value of 4,439 which means that the t-count is greater than the t-table value of 1.9837 and has a sig value. t for the motivation variable of 0.013 is smaller than the alpha of 0.05. This shows that the motivation variable has a positive influence on the effectiveness of employees at the Medan City Transportation Agency. Then the alternative hypothesis is accepted. The Organizational Citizenship Behavior variable has a t-count value of 3.128, which means that the t-count is greater than the t-table value of 1.9837 and has a sig value. t for the Organizational Citizenship Behavior variable is 0.002 smaller than the alpha of 0.05. This shows that the Organizational Citizenship Behavior variable has a positive influence on the effectiveness of employees at the Dinas Perhubungan Kota Medan. Then the alternative hypothesis is accepted.